Effect of rotor magnetic isolation dimensions on no‐load performance of ultra‐low speed high torque spoke type permanent magnet motor - Shaonan Sun; Guihong Feng; Yan Li; Bingyi Zhang (IET Electric Power Applications)
Abstract This study investigates the effects of rotor magnetic isolation dimensions on the no‐load performance of ultra‐low speed high torque spoke type permanent magnet motor. The studied spoke type permanent magnet motor structures are shown, where the rotor magnetic isolation parts include a magnetic barrier near the air gap (MB‐NAG), a magnetic barrier near the magnetic isolation sleeve (MB‐NMIS), a magnetic isolation sleeve (MIS). The magnetic circuit model is performed and the finite element analysis method is used to analyse the no‐load performance. Through analysing no‐load performance with three MB‐NAG shapes, the way to narrow the optimise dimension range considering reducing the cogging torque and increasing the back‐EMF synchronously is concluded. The results with different MB‐NMIS and MIS dimensions show that: (a) the optimised MB‐NMIS dimensions can increase the back‐EMF with a thin MIS in a certain dimension range of MB‐NMIS, and (b) the increasing proportion of back‐EMF influenced by the MB‐NMIS is inversely proportional to the thickness of MIS. The feasibility and effectiveness of the proposed motor structure and conclusion are experimentally verified.